Effects of preservation of rat lungs in a hypothermic medium on alveolar morphology - (:unkn) unknown (URBAN & FISCHER VERLAG, 1999)
The increasing use of organs such as liver, lung, heart, pancreas, kidney and small intestine for transplantation purposes necessitates the development of optimum preservation techniques. The aim of our study was to investigate time-related morphological changes in alveoli during preservation of rat lungs in hypothermic Euro-Collins solution. Lungs were perfused via the pulmonary arteries with Euro-Collins solution at a temp of 19 degrees C. Totally perfused lungs were placed in Euro-Collins solution and stored for 6, 12 and 24 h at 4 degrees C. Biopsies were taken and prepared for examination at the light and electron microscopical level. Light microscopic examination revealed good preservation of the alveoli after storage for 6 h and moderate damage of alveolar architecture after 12 h of preservation. Severe degeneration of alveoli was found after 24 h of storage. The main ultrastructural changes were observed in lungs stored for 12 h and 24 h. After 6 h of storage, tissue damage was not found. Pneumocytes type II lost their apical microvilli and lamellar bodies were electron-lucent, indicating lamellar degeneration after 12 and 24 h of storage. Pneumocytes type I were also damaged. Their cytoplasm contained many vacuoles. Endothelial lining of the capillaries was contracted. Endothelial cells also showed many vacuoles. Edema around the capillaries was observed. We conclude on the basis of our morphological study, that Euro-Collins solution at low temperature is a good preservative for a short period of time only, but serious tissue damage occurs after periods of preservation longer than 12 h.
Keywords: lung injury; preservation; transplantation; alveoli; pneumocytes; Euro-Collins; OF-WISCONSIN SOLUTION; EURO-COLLINS SOLUTION; EXTRACELLULAR FLUID; LIVER PRESERVATION; TRANSPLANTATION; STORAGE; EUROCOLLINS; DAMAGE